Response of Dung Beetle Communities (Coleoptera: Scarabaeidae) Across Gradient of Disturbance in the Tropical Lowland Forest of Buton, Sulawesi - Mariana Silvana Moy; Ani Mardiastuti; Sih Kahono (ZOO INDONESIA, 2016)
Little is known about how antropogenic disturbance triggered the biodiversity loss of functionally important insect groups in an island, including dung beetle (Coleoptera: Scarabaeidae). This study focused on the responses of dung beetle across gradient of disturbance in a secondary tropical lowland rainforest (Lambusango forest, Sulawesi, Indonesia). From June to August 2013, dung beetles were collected in the forest with low, intermediate, and high level of disturbances. Each disturbance level had three transects which were separated at least 500 m each other (n=9). Ten pitfall traps per transect baited with cattle dung were set, along 100 m transect for 48 hours. A total of 1.710 dung beetles, representing 29 species, were collected. Total 79% trapped specimens and 55% of species richness was found in the intermediate dis-turbance, which it was significantly differed compare to two other disturbances. Shannon-Wienner index was signifi-cantly higher in low disturbance than in intermediate and high disturbance, while dominance speciesindex mostly occured in intermediate disturbance. A two-dimensional scalling plot based on Bray-Curtis index indicated the different species composition of the beetles between disturbance levels. We concluded that dung beetle assemblages of secondary lowland rainforests appeared a robust respond to the disturbance levels.